معالم التجربة الروحية بين البوذية وصوفية الإسلام : دراسة مقارنة - ماشطة أحمد (International Islamic University Malaysia, 2007)
This study attempts to highlight the aspects and essences of mystical experience in the teachings of Buddhism and Islamic mysticism. It discusses the concept of spirituality in Buddhism and Islamic mysticism, and its significance in the two religions. The study also exposes the aspects and essences of mystical experience, and the path to attain salvation in the teachings of Buddhism and inner tranquility and purity in Sufism. The study also aims at highlighting points of convergency and dissimilarities between Buddhism and Sufism in the dimension of spirituality. The study follows an analytical approach, whereby the spiritual issues in the two religions were analysed from the primary and secondary sources, in English and Arabic. In presenting the teachings and practices of both Buddhism and Sufism, descriptive method was applied. Meanwhile, the historical method was also utilized to explore the historical background of the development of Buddhism and Islamic mysticism. Inductive and comparative methods were applied to analyse the teachings and practices of Buddhism and Sufism, and their path to attain salvation i.e. nibbana in Buddhism, and fana’ in Islamic Mysticism. The study concludes that despite the differences there are some points of convergency in the aspects of spirituality in the two religions. The Buddhist and Sufis mystical paths are close to each other. This can be seen obviously in their practices and methods of the purification of the soul, where the followers of both Buddhism and Islamic Mysticism are bound with the strict rules that govern their spiritual life, such as “master and adept rules”, living in shared communities, living a life of constant vigilance, isolation, poverty, celibacy and concentrated contemplation. Both mysticisms also share the similar ultimate goal in their spiritual endeavour, that is realization of the inner-content and satisfaction.